Evaluation of the effect of valence state on cerium oxide nanoparticle toxicity following intratracheal instillation in rats. Issue 7 (8th August 2016) - Dunnick, Katherine M.; Morris, Anna M.; Badding, Melissa A.; Barger, Mark; Stefaniak, Aleksandr B.; Sabolsky, Edward M.; Leonard, Stephen S.
Abstract: Cerium (Ce) is becoming a popular metal for use in electrochemical applications. When in the form of cerium oxide (CeO2 ), Ce can exist in both 3 + and 4 + valence states, acting as an ideal catalyst. Previous in vitro and in vivo evidence have demonstrated that CeO2 has either anti- or pro-oxidant properties, possibly due to the ability of the nanoparticles to transition between valence states. Therefore, we chose to chemically modify the nanoparticles to shift the valence state toward 3+. During the hydrothermal synthesis process, 10 mol% gadolinium (Gd) and 20 mol% Gd, were substituted into the lattice of the CeO2 nanoparticles forming a perfect solid solution with various A-site valence states. These two Gd-doped CeO2 nanoparticles were compared to pure CeO2 nanoparticles. Preliminary characteristics indicated that doping results in minimal size and zeta potential changes but alters valence state. Following characterization, male Sprague-Dawley rats were exposed to 0.5 or 1.0 mg/kg nanoparticles via a single intratracheal instillation. Animals were sacrificed and bronchoalveolar lavage fluid and various tissues were collected to determine the effect of valence state and oxygen vacancies on toxicity 1-, 7-, or 84-day post-exposure. Results indicate that damage, as measured by elevations in lactate dehydrogenase, occurred within 1-day post-exposure and was sustained 7-day post-exposure, but subsided to control levels 84-day post-exposure. Furthermore, no inflammatory signaling or lipid peroxidation occurred following exposure with any of the nanoparticles. Our results implicate that valence state has a minimal effect on CeO2 nanoparticle toxicity in vivo .